LARGE N AND CONFINING FLUX TUBES AS STRINGS - A VIEW FROM THE LATTICE - Teper, M (2009)
I begin this paper by describing some of the useful things that we have learned about large-N gauge theories using lattice simulations. For example that the theory is confining in that limit, that for many quantities SU(3) ≃ SU(∞), and that this includes the strongly coupled gluon plasma just above T c, thus providing some justification for the use of gauge-gravity duality in analysing QCD at RHIC/LHC temperatures. I then turn, in a more detailed discussion, to recent progress on the problem of what effective string theory describes confining flux tubes. I describe lattice calculations of the energy spectrum of closed loops of confining flux, and some dramatic analytic progress in extending the 'universal Luscher correction' to terms that are of higher order in 1=l 2, where l is the length of the string. Both approaches point increasingly to the Nambu-Goto free string theory as being the appropriate starting point for describing string-like degrees of freedom in SU(N) gauge theories.